2013
DOI: 10.1111/j.1540-5850.2013.12007.x
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Budget Requirements and State Spending: A Long–Panel Study

Abstract: This study tests the effects of balanced budget requirements on three measures of state expenditure using data on 48 states for the years 1950–2004. We find that the following rules are effective in constraining expenditures: (1) requiring that the governor submits a balanced budget; (2) placing controls on supplemental appropriations; and (3) prohibiting the carry‐over of a deficit from one fiscal year or biennium into the next. The latter two rules exert larger individual effects than the first. All else equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 33 publications
(61 reference statements)
1
33
0
2
Order By: Relevance
“…Given the warnings made regarding the impact of the design of fiscal rules on the response of the agents (Azzimonti et al, 2016;Smith and Hou, 2013;Flynn and Pessoa, 2014), the study first identified the relevant dimensions -classification -of the carry-over regulation as it is adopted in Brazil.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the warnings made regarding the impact of the design of fiscal rules on the response of the agents (Azzimonti et al, 2016;Smith and Hou, 2013;Flynn and Pessoa, 2014), the study first identified the relevant dimensions -classification -of the carry-over regulation as it is adopted in Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…The main issue is how constitutional rules for fiscal discipline are effective (Smith and Hou, 2013;Azzimonti et al, 2016), and whether to adopt more or less rigid budgetary rules. Some studies point out that a no deficit carry-over rule (Bohn and Iman, 1996:8) is a more effective rule in comparison to others, when it comes to containing expenses and achieving a balanced budget (Smith and Hou, 2013). However, harsh budget-balancing rules may lead policymakers to take other unregulated actions to deal with fiscal crises, such as asset sales or accounting manipulation, as observed by Costello et al (2017) in state governments in the United States.…”
Section: Literature On Budget Carry-overmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of state‐level budgeting challenges suggest similar challenges, as shown by Dautrich et al () for Connecticut, Lauth () for Georgia, Bunch () for Illinois, and Bifulco and Duncombe () for New York. Hou and Smith (, ) and Smith and Hou () have shown that technical rules governing budgetary outcomes can be more effective than political rules dictating the political process of assembling and approving budgets. However, enacting technical rules requires a shared normative commitment that transcends political differences.…”
Section: Motivationmentioning
confidence: 99%
“… Smith and Hou () have an alternative measure of budget stringency, but they refuse to make their data publicly available.…”
mentioning
confidence: 99%